KONTRIBUSI SIS (SISTEM INFORMASI SANTRI) DALAM INOVASI MANAJEMEN KEUANGAN PONDOK PESANTREN - Siti Aimah; Liqo Mursidah (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2021)
The objectives set from this study are: (1) To find out the planning of SIS in the financial management of Blokagung Tegalsari Banyuwangi Islamic Boarding School, (2) To find out the supporting and inhibiting factors of the application of SIS in the financial management of Blokagung Tegalsari Banyuwangi Islamic Boarding School. This research uses descriptive qualitative research methods. The research was the researcher himself who became an instrument (human instrument) with supporters of the interview guide grid. Data collection is more emphasized on observation, interview, and documentation. The validity of the data in this study uses data triangulation.The results of his research: SIS (SantriInformation System) as an innovation in the financial management of the Darussalam Boarding School Blokagung Tegalsari Banyuwangi is implemented with several stages which include: (1) Determination of payment system innovation, (2) Determination of santri payment budget.(3) Appointment of the system responsible team. (4) Appointment of a payment system service team.supporting and inhibiting factors of the application of SIS to the financial management of the Darussalam Boarding School, Blokagung Tegalsari Banyuwangi, they are: Supporting factors (1) Productivity of the person in charge, (2) Socialization strategies for implementing SIS. Inhibiting factors: (1) Lack of supporting facilities, (2) Timeliness of payment reporting.